Lesiones genitales, paragenitales y extragenitales en delitos de violencia sexual femenina en atención primaria en salud. - Poma Carpio, Domenica Paulette (Machala : Universidad Técnica de Machala, 2022)
Introduction: The Organic Comprehensive Criminal Code of Ecuador (COIP) defines sexual violence as "the person who, as a manifestation of violence against women, interferes with another and forces her to have sexual relations and other similar practices"; a fatal outcome in a case of violence is death, which, due to resistance to the attack, the victims die from strangulation, trauma or bleeding wounds. Objective: To differentiate genital, paragenital and extragenital injuries in crimes of female sexual violence through a systematic review of the literature that contributes to the resolution of legal medical processes. Methodology: This is a study carried out in a retrospective descriptive manner through a bibliographic review in the scientific bases of SCIELO, EBSCO, PUBMED, MESH, for the extraction of qualitative information by collecting information on genital injuries in cases of sexual violence. Results: 27 articles were found, of which 20 articles correspond to quartile 1, 5 articles to quartile 2 and also 3 books about legal medical foundations. Conclusion: According to the literature reviewed, the role of the doctor is reaffirmed when receiving a patient who is a victim of rape; The professional who captures the patient must perform an exhaustive physical examination that determines lesions in the genital, paragenital and extragenital areas; procedure that is mandatory and that must be detailed in the respective clinical history.
Introducción: El Código Orgánico Integral Penal del Ecuador (COIP) define a la violencia sexual como “la persona que, como manifestación de violencia contra la mujer, se interponga a otra y la obligue a tener relaciones sexuales y otras prácticas análogas”; un desenlace fatal en un caso de violencia es la muerte, que, por resistencia al ataque, las victimas mueren por estrangulación, traumatismos o heridas sangrantes. Objetivo: Diferenciar las lesiones genitales, paragenitales y extragenitales en delitos de violencia sexual femenina mediante una revisión sistemática de la literatura que contribuya a la resolución de procesos médicos legales. Metodología: Se trata de un estudio realizado de manera descriptiva retrospectiva a través de una revisión bibliográfica en las bases científicas de SCIELO, EBSCO, PUBMED, MESH, para extracción de información cualitativa recopilando información de lesiones genitales en casos de violencia sexual. Resultados: Se encontraron 27 artículos, de los cuales 20 artículos corresponde al cuartil 1, 5 artículos cuartil 2 y además 3 libros acerca de los fundamentos médico legales. Conclusión: De acuerdo a la literatura revisada se reafirma el rol del médico al momento de receptar a una paciente que es víctima de violación sexual; el profesional que capta a la paciente debe realizar un examen físico exhaustivo que determine lesiones en el area genital, paragenital y extragenital; procedimiento que es obligatorio y que debe estar detallado en la respectiva historia clinica.
Keywords: AGRESIONES SEXUALES; VIOLENCIA SEXUAL; DELITOS SEXUALES.